A sustainable cruise ship development with cleaner production of electricity, heat, cooling, freshwater and hydrogen - Asal, Sulenur; Acir, Adem; Dincer, Ibrahim (ELSEVIER SCI LTD, 2024)
In this present study, the main aim is to design a novel sustainable cruise ship and analyze the multigeneration system with all subsystems using the first and second laws of thermodynamics. The present multigeneration system is modeled to meet the requirements of the cruise ship, including electricity, heating, cooling, and freshwater. The present integrated system comprises the combined Brayton-Rankine cycle, the multi-effect desalination system, the reverse osmosis desalination system, the ammonia-water absorption refrigeration system, the cobalt-chlorine thermochemical cycle, the Darrieus wind turbines, the solar photovoltaic modules, and the proton exchange membrane electrolyser. The system analyses, simulations, and assessments are carried out using the Engineering Equation Solver, the Aspen Plus, the System Advisor Model, and the PVsyst software packages interactively and comprehensively. Consequently, approximately 142.14 MWh total of electricity is generated by the combined Brayton-Rankine cycle, the Darrieus wind turbines, and the solar photovoltaic modules. The cobalt-chlorine cycle produces 0.0017 kg/s hydrogen, and 0.0007 kg/s hydrogen is produced by proton exchange membrane electrolyser. Moreover, 5.9 MWh of cooling load and 1.5 MWh of heating load are met via the ammonia-water absorption refrigeration system and the waste heat from the Rankine cycle. The desalination system is designed to produce a total of 9180 tons of freshwater. Furthermore, the energy and exergy efficiencies of the overall system are calculated as 16.89% and 15.35%, respectively.
Keywords: Cleaner production; Cruise ship; Sustainability; Multigeneration; Energy; Exergy; Electricity; Heat; Cooling; Freshwater; Hydrogen; POWER-SYSTEM; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology